The archive’s moment - Caimari, Lila Maria (2021)
This article summarizes observations on the “archive question” as it manifests itself in Argentina at the present moment. Based on a presentation delivered in Buenos Aires, it opens with a general appraisal of the multiple dynamics (political, disciplinary, technological) converging on this issue. Then, it focuses on a particular dimension of this process—namely, the impact of the digital archive on the reconstruction of the Argentine past.